Teologia usa saias? mulheres na teologia - da exclusão à profissionalização - Rivas, Maria Elise Gabriele Baggio Machado (2014)
The aim of our work is to analyze the professional field of Theology after the regulation for women, considering that the formal status of the graduation course in Theology has provided an aspect of equality, and defined the vocational training and career.The formalization of the course of Theology, approved by the Ministry of Education and Culture, provides a new situation concerning the religious training as well as the vocational training path. When Theology was recognized as a discipline, it consequently turned to be ruled by the educational system of the country, allowing everyone to apply for the course, and to take it as a career. Taking into account this new situation, this dissertation intends to discuss the professionalization for women in the field of Theology in the context of patriarchy.Our sources include interviews with graduated and undergraduated students from five different institutions officially authorized by the Ministry of Education and Culture in the city of São Paulo in order to verify whether changes occurred for the female theologians and their careers